Managing public services--implementing changes a thoughtful approach to the practice of management - Doherty, Tony L. (London Routledge, 2002)
Focusing on change as a constant factor in the management of any organization, this informative book helps the student and practitioner to develop the skills and knowledge they require to underpin the work of a modern service manager in rapidly-changing public sector organizations - whether publicly owned, privately managed or sub-contracted.
Includes bibliographical references (p. [533]-535)
Keywords: Public administration